PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI USAHA DAN ENERGI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS X IPA SMA NEGERI 7 WAJO - Khumasiah, Sakka (Inspiratif Pendidikan, 2019)
Physics lessons are more often presented using the lecture method, so students become less active. Therefore, it is necessary to look for alternative methods that are more challenging for students to develop their potential. The learning model chosen by the author is cooperative learning type Student Team Achievement Division (STAD). This research was conducted at Wajo 7 Public High School, in class X IPA, with the aim of: (1) Increasing Student Activity and Learning Outcomes in Business and Energy material through the application of cooperative learning Type Student Team Achievement Division (STAD) (2) Knowing the benefits of learning cooperative type STAD for students, teachers and classes. The results found that: (1) STAD type cooperative learning makes students active, confident, developed cooperation and skilled in expressing opinions. (2) STAD type cooperative learning can improve student learning outcomes in Business and Energy material in class X IPA of SMA Negeri 7 Wajo. (3) Cooperative learning type STAD can also make learning from the teacher be directed and systematic.